Anaerobic threshold determination on youth football players in tests with and without ball - Bertucci, Danilo Rodrigues [UNESP]; Demarchi, Danilo; Frade Sousa, Nuno Manuel; Baldissera, Vilmar (Inst Brasileiro Pesquisa & Ensino Fisiologia Exercicio-ibpefex, 2018)
Higher anaerobic threshold (AT) means, theoretically, that a player could maintain a higher average intensity in an activity without accumulation of lactate. Thus, the aim of study was to identify the velocity in AT (VAT) in young football players in an incremental test (IT) with/without the domain of the ball during the test. Sixteen adolescents (mean +/- SD, 14.5 +/- 0.5, 58.0 +/- 6.7 kg, 158 +/- 11 cm and BMI 22.9 +/- 1.2 kg/m(2)) and they are divided in two group control group (CG, n = 8) and exercise group (EG, n = 8). The incremental test (IT) on training field, which consisted in stages begun in 7km/h with increasing speed of 1km/h every two minutes. The EG performed the IT with the domain of the ball during the test and the CG performed the same situation without ball domain. VAT (km/h) and blood lactate concentration in VAT (mmol/L) were not significantly different (EG, 10.9 +/- 1.1 and CG, 11.3 +/- 0.7 with p = 0.250) and (EG, 3.4 +/- 1.0 and CG, 2.9 +/- 0.7 with p = 0.368) respectively. However, Borg scale in VAT was significantly different (EG, 17.5 +/- 0.5 and CG, 14.5 +/- 0.5 star with p = 0.005), it represents change in their perceived exertion, somewhat hard to very hard. The involvement with ball, was not sufficient to change VAT or blood lactate concentration on VAT, but, this situation may affect the rating of perceived exertion in young players.
Keywords: Lactate threshold; Incremental test; Borg scale